Implementation of Business Ethics in Snack Buying and Selling Practices at TB MART from a Sharia Economic Perspective - M.Khoirul Mustofa (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze in depth the implementation and exploration of Islamic business ethics in the practice of buying and selling in a modern retail organization at TB MART Darussalam, Indonesia, in order to mitigate the discrepancy between the theological norms of Islamic economics and the reality of contemporary market behavior. Using a qualitative approach with a case study type, data were collected through in-depth interviews, participant observation, documentation, and audio analysis of 6 informants including store managers, cashiers, sales assistants, and regular customers. The results of the study indicate that TB MART Darussalam has successfully internalized Islamic norms into its organizational social structure so that business ethics manifests as automatic behavior (habitualization). This actualization is evidenced through three main operational aspects: first, the implementation of quality transparency (tabyin) in the form of providing